2012
DOI: 10.7577/pp.v2i1.19
|View full text |Cite
|
Sign up to set email alerts
|

Work–Family Interference: Nurses in Norway and Finland

Abstract: Abstract:The aim of the study is to investigate the level of work-family interference (WFI) for part-time nurses in Norway and Finland. Part-time work is usually cited as a desirable way in which to facilitate work and family harmony. However, the opportunity to work part-time in professions may be associated with greater difficulties and challenges than commonly presumed. Part-time professionals are often stigmatized as being less committed to work and report fewer job rewards than colleagues in full-time pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…In the reviewed papers, the differential aspects of WFC were concerned with cultural, job organization, gender and age variables. For cultural and social differences, Abrahamsen et al (2012) found a slightly higher level of WF interference for hospital nurses in Finland than in Norway. The level of WF interference for Norwegian nurses increased with extended part-time work, and for nurses in Finland with long hours.…”
Section: Differential Aspects Of Wfcmentioning
confidence: 87%
See 3 more Smart Citations
“…In the reviewed papers, the differential aspects of WFC were concerned with cultural, job organization, gender and age variables. For cultural and social differences, Abrahamsen et al (2012) found a slightly higher level of WF interference for hospital nurses in Finland than in Norway. The level of WF interference for Norwegian nurses increased with extended part-time work, and for nurses in Finland with long hours.…”
Section: Differential Aspects Of Wfcmentioning
confidence: 87%
“…All papers presented empirical research, and in some of them, the report was part of a wider study. For instance, in the study by Abrahamsen et al (2012), the data were gathered as a part of the European Nurses Early Exit Study. Also, those in the study by were part of the "Be Well Work Well" study conducted by the Harvard School of Public Health, Center for Work, Health and Wellbeing.…”
Section: Methodological Aspects Of the Articles Reviewedmentioning
confidence: 99%
See 2 more Smart Citations
“…In developed countries, work-life balance has long been at the forefront of policy discourse (Abrahamsen et al, 2012;Craig & Sawrikar, 2009;Gregory & Milner, 2009). A key question in the work-life debate concerns the extent to which patterns reflect valueoriented choices or are a consequence of social and structural constraints.…”
Section: Working Hours: Preferences and Constraintsmentioning
confidence: 99%